A technical note on intra-arterial cone-beam computed tomography for the evaluation of flow-diverter stents: Image quality differences between diluted and non-diluted contrast medium. Issue 2 (April 2020) - Kocer, Naci; Kandemirli, Sedat G; Ruijters, Daniel; Mantatzis, Michalis; Kizilkilic, Osman; Islak, Civan
Background: Design of flow-diverter stents for flexibility, tractability, and low profile limits their radiopacity on conventional digital subtraction angiography. Cone-beam computed tomography (CBCT) offers higher spatial resolution for the evaluation of flow-diverter stents. However, CBCT requires optimal dilution and timing of contrast medium for simultaneous visualization of the stent, arterial lumen, and vessel wall. There are only limited data on the effects of different contrast dilutions on CBCT image quality in neurointerventional applications. Materials and methods: In our institution, intra-arterial CBCTs were acquired during stent deployment and at follow-ups with 10% diluted contrast. We had recently started acquiring intra-arterial CBCTs with non-diluted contrast. Retrospective analysis of our flow-diverter data identified eight cases with different aneurysm locations who had intra-arterial CBCT with 10% diluted contrast immediately after flow-diverter stent deployment and with non-diluted contrast technique during follow-ups. For each case, the image quality between diluted and non-diluted contrast techniques was compared qualitatively by assessing stent visualization and quantitatively by plotting gray-scale intensity values along the vessel lumen. Results: In two sets of CBCT images per each case, there was no substantial difference between diluted and non-diluted CBTC techniques for the evaluation of stent architecture and lumen opacification. Gray-scale intensity values perpendicular to the lumen revealed similar intensity values along the neighboring parenchyma, vessel wall, and lumen for the two different contrast techniques. Conclusion: Intra-arterial CBCT angiography can be performed without contrast dilution and still achieve adequate image quality in certain cerebral aneurysms treated with flow diverter. The non-diluted contrast technique avoids the time loss during preparation of diluted contrast and installation of diluted contrast to the injector in angiography suites with a single power injector.